KONFIGURASI IDENTITAS NASIONAL, NASIONALISME DALAM ERA GLOBALISASI SUATU HARAPAN DAN TANTANGAN - Suryono, Hassan (MIIPS, 2008)
Indonesians existence is affected by the nationalist attitude that loves Indonesian country and motherland. Globalization not only affects the positive and negative aspects of youth value, norm and behaviour but also affects the societal and national life in the political, economic and social cultural aspects. Globalization makes Indonesian nation needs to revitalize the values that will become a reference for overall development. In order to minimize the negative effect, there should be a preventive and repressive attempt. Preventive attempt is conducted by undertaking students/young generation building in order to have nationality mentality, soul and spirit. Meanwhile repressive attempt is conducted by taking an action and by nullifying the factors having negative influence. The positive influence is not received randomly, but it should be selected in order not to deviate from Indonesian nations identity.